2007
DOI: 10.1111/j.1439-0434.2007.01307.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Phenolic Compounds in Pea (Pisum sativum L.) Inoculated by Rhizobium leguminosarum and Infected with Orobanche crenata

Abstract: Parasitic plants are among the most important problematic weeds, they are responsible of major losses of many crops. Early growth stages, such as seed germination stimulated by host root exudates and tubercle development, are key phases for these parasites development. Inhibition of these early phases could be a general strategic option for parasitic plants management. In our previous study, we have demonstrated that some Rhizobium leguminosarum strains decrease pea infection by Orobanche crenata and germinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Rhizobial inoculation of legumes reduces the seed-germination activity of root exudates on Orobanche (Mabrouk et al 2007). By mixing root exudates of a rhizobial pea plant with a GR-24 solution, Mabrouk et al (2007) showed that the reduced seed-germination activity of the root exudates of rhizobial pea plants on O. crenata is at least partially due to the presence of seed germination inhibitors in those exudates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rhizobial inoculation of legumes reduces the seed-germination activity of root exudates on Orobanche (Mabrouk et al 2007). By mixing root exudates of a rhizobial pea plant with a GR-24 solution, Mabrouk et al (2007) showed that the reduced seed-germination activity of the root exudates of rhizobial pea plants on O. crenata is at least partially due to the presence of seed germination inhibitors in those exudates.…”
Section: Discussionmentioning
confidence: 99%
“…Rhizobial inoculation of legumes reduces the seed-germination activity of root exudates on Orobanche (Mabrouk et al 2007). By mixing root exudates of a rhizobial pea plant with a GR-24 solution, Mabrouk et al (2007) showed that the reduced seed-germination activity of the root exudates of rhizobial pea plants on O. crenata is at least partially due to the presence of seed germination inhibitors in those exudates. However, in our experiments, the combination of root exudates of nonmycorrhizal or mycorrhizal cowpea BR1 with water did not result in an increase in Striga seed germination, suggesting that mycorrhization did not lead to an increased production of compounds inhibitory to Striga seed germination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…conceive root exudates of their host plants as a signal to germinate and subsequently infect the host. Mabrouk et al () assessed the interaction of rhizobia ( Rhizobium leguminosarum ), pea root exudates, and broomrape and found that the germination rate of broomrape seeds significantly decreases in the presence of root exudates collected from rhizobia inoculated peas. They identified marked changes in root exudate composition following inoculation with rhizobia, notably with significantly higher exudation of various phenolic compounds and flavonoids.…”
Section: The Role Of Root Exudates In Disease Resistance Of Legumesmentioning
confidence: 99%
“…Mabrouk et al . () also have shown that some Rhizobium leguminosarum strains decrease O. crenata infections in pea by inducing systemic resistance.…”
Section: Integrated Broomrape Managementmentioning
confidence: 90%